Quality of Work life of Nurses in a Government Hospital, Chitwan - Rai, Aakriti; Lamichhane, Shila; Chaudhary, Tanuja Kumari; Brooks, Beth A (Med Phoenix, 2023)
Introduction: Work is an integral part of life where employees spend about one third of their entire life in workplace, thus working environment must be favorable. When the quality of work-life is stable, productivity is bound to increase. It seeks to benefit employees, their families, and the organization as well. The objective of the study is to identify the quality of work life of nurses working in Bharatpur hospital, Nepal. Materials and Methods: A descriptive cross sectional study design was used. The total number of 84 nurses from Bharatpur Hospital were purposively selected. Non-probability convenience sampling techniques was used to select a nurse working in Bharatpur Government hospital, Bharatpur, Chitwan having maximum of 6months job experience. Data were collected using standardized Brooks’ Quality of Nursing Work Life Survey tool. Data were analyzed using the statistical package of social science(SPSS) version 20.0. Inferential statistic was used to measure the association between quality of life of nurse and selected variables. Results: The study revealed that overall quality of work life were moderate (79.8%) of respondents. The findings on dimension wise quality of work life of nurses were 83.3%, 67.3% and 65.5% of respondents had moderate level of quality in work design, home life/ work life and work world dimension respectively, while 57.1% of respondents had high level of quality of work life of nurses in work context dimension. The Quality of Work Life of nurses was associated with level of education (χ2=11.027, p= 0.004). Conclusions: The majority of nurse had moderate level quality of work life. The authorities in the health care system should develop strategies for improving the nurses work conditions and their quality of work life so that, nurses will be able to perform quality care for their patients.